Implementasi Good Governance dalam Pengelolaan Pelayanan Keimigrasian di Indonesia - Agung Setiawan; Aninda Sri Rahayu Mastur; Rahmawati Nurul Jannah (Jurnal Media Administrasi, 2025)
This study aims to analyze the reform of Indonesia’s immigration policy in the era of globalization and to compare it with the immigration policies of other ASEAN countries, such as Malaysia, Singapore, and Thailand. The research uses a literature review method by analyzing current regulations, international reports, and academic publications. The findings indicate that Indonesia has made significant reforms through immigration service digitalization, the implementation of e-visas, and a human rights-based approach. However, compared to neighboring countries, Indonesia still faces challenges in inter-agency coordination, undocumented migrant regulation, and refugee protection. The comparative study reveals that ASEAN countries adopt varied approaches, from merit-based systems to migrant regularization programs. This research concludes that Indonesia has great potential to lead the harmonization of migration policies in the ASEAN region, but it requires stronger legal frameworks and more integrated governance.